Characterization of the genomic features and expressed fusion genes in micropapillary carcinomas of the breast. Issue 5 (5th February 2014) - Natrajan, Rachael; Wilkerson, Paul M; Marchiò, Caterina; Piscuoglio, Salvatore; Ng, Charlotte KY; Wai, Patty; Lambros, Maryou B; Samartzis, Eleftherios P; Dedes, Konstantin J; Frankum, Jessica; Bajrami, Ilirjana; Kopec, Alicja; et al.
Abstract Micropapillary carcinoma (MPC) is a rare histological special type of breast cancer, characterized by an aggressive clinical behaviour and a pattern of copy number aberrations (CNAs) distinct from that of grade‐ and oestrogen receptor (ER)‐matched invasive carcinomas of no special type (IC‐NSTs). The aims of this study were to determine whether MPCs are underpinned by a recurrent fusion gene(s) or mutations in 273 genes recurrently mutated in breast cancer. Sixteen MPCs were subjected to microarray‐based comparative genomic hybridization (aCGH) analysis and Sequenom OncoCarta mutation analysis. Eight and five MPCs were subjected to targeted capture and RNA sequencing, respectively. aCGH analysis confirmed our previous observations about the repertoire of CNAs of MPCs. Sequencing analysis revealed a spectrum of mutations similar to those of luminal B IC‐NSTs, and recurrent mutations affecting mitogen‐activated protein kinase family genes and NBPF10. RNA‐sequencing analysis identified 17 high‐confidence fusion genes, eight of which were validated and two of which were in‐frame. No recurrent fusions were identified in an independent series of MPCs and IC‐NSTs. Forced expression of in‐frame fusion genes (SLC2A1–FAF1 and BCAS4–AURKA) resulted in increased viability of breast cancer cells. In addition, genomic disruption of CDK12 caused by out‐of‐frame rearrangements was found in one MPC and in 13% of HER2‐positive breast cancers, identified through a re‐analysis of publicly available massively parallel sequencing data. In vitro analyses revealed that CDK12 gene disruption results in sensitivity to PARP inhibition, and forced expression of wild‐type CDK12 in a CDK12‐null cell line model resulted in relative resistance to PARP inhibition. Our findings demonstrate that MPCs are neither defined by highly recurrent mutations in the 273 genes tested, nor underpinned by a recurrent fusion gene. Although seemingly private genetic events, some of the fusion transcripts found in MPCs may play a role in maintenance of a malignant phenotype and potentially offer therapeutic opportunities. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.